Increased CD163+ Macrophage Activation and High Expression of CD163 Promote Granulosa Cell Apoptosis in Polycystic Ovary Syndrome - Ye J; Wang S; Wang Z; Jiang Y; Jia J; Yang Y; Huo L; Liu X; Zhou Y; Yang Z; Mao J; Ma Y; et al. (Journal of Inflammation Research, 2025)
Jixian Ye,1,* Shang Wang,2,* Zhaoyu Wang,1,* Yuyun Jiang,1 Jue Jia,3 Yanwei Yang,1 Liyue Huo,1 Xi Liu,1 Yuepeng Zhou,1 Zhe Yang,1 Jiahui Mao,1 Yongbin Ma,1,4 Xuefeng Wang1,5 1Department of Central Laboratory, The Affiliated Hospital of Jiangsu University, Zhenjiang, 212001, People’s Republic of China; 2Tzu Chi International College of Traditional Chinese Medicine, Vancouver, BC, Canada; 3Department of Endocrinology and Metabolism, The Affiliated Hospital of Jiangsu University; Institute of Endocrine and Metabolic Diseases, Jiangsu University, Zhenjiang, 212001, People’s Republic of China; 4Department of Central Laboratory, Jintan Hospital, Jiangsu University, Jintan, 213200, People’s Republic of China; 5Department of Nuclear Medicine, The Affiliated Hospital of Jiangsu University; Institute of Digestive Diseases, and Institute of Endocrinology and Metabolic Diseases, Jiangsu University, Zhenjiang, 212001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuefeng Wang, Email xuefengwang@ujs.edu.cn Yongbin Ma, Email mayongbin2009@163.comBackground: The inflammatory microenvironment disrupts the ovarian niche, impairing granulosa cell function and leading to aberrant follicular development, a key pathological feature of polycystic ovary syndrome (PCOS). However, the precise mechanisms by which inflammation influences granulosa cell function remain poorly understood.Methods: Differentially expressed genes (DEGs) were identified from the GSE34526 dataset, with the inflammatory marker CD163 selected for further investigation due to its upregulation in ovarian granulosa cells in PCOS. Serum levels of soluble CD163 (sCD163) were measured in patients with PCOS, and a dehydroepiandrosterone (DHEA)-induced PCOS mouse model was utilized to examine the relationship between CD163 expression, inflammatory mediators, and macrophage activity in the ovaries and uterus. Granulosa cell apoptosis, inflammatory cytokine secretion, and sCD163 release from conditioned media (CM) of differently polarized macrophages co-cultured with COV434 cells were assessed.Results: Elevated serum sCD163 levels were observed in patients with PCOS. The DHEA-induced PCOS mice exhibited characteristic oestrous cycle abnormalities, as well as morphological and pathological alterations in the ovaries and uterus. Increased CD163 expression was detected in ovarian and uterine macrophages of PCOS mice, alongside elevated inflammatory cytokines. Conditioned media from M1-polarized macrophages induced apoptosis in COV434 granulosa cells, with concomitant increases in pro-inflammatory cytokines (IL-1β and IL-6) and sCD163 secretion. Furthermore, CD163+ cell apoptosis was heightened in the ovaries of PCOS mice.Conclusion: These findings suggest that ovarian macrophages, through elevated CD163 expression, contribute to granulosa cell apoptosis and the secretion of sCD163, which may play a critical role in the pathogenesis of PCOS. Keywords: CD163, high expression, macrophage activation, granulosa cell apoptosis, polycystic ovary syndrome